2011
DOI: 10.1136/thoraxjnl-2011-201054b.136
|View full text |Cite
|
Sign up to set email alerts
|

S136 The association between cough reflex sensitivity and serum ACE level in patients with sarcoidosis

Abstract: key determinants of smoking, gender, DM, HTN, hypercholesterolaemia and BMI. On univariate analysis, BMI was significantly higher in the NSIP subgroup (p¼0.025 vs UIP or INDET). Rates of STEMI and strokes were highest in UIP cases (n/s) whereas that of CABG was highest in the INDET subgroup. These observations were corrected for IPF severity in so far as FVC and DL CO were decreased comparably across all three radiological subgroups. Evaluation of co-existing COPD was not undertaken; however, mean FEV 1 did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In the study by Sinha et al, patients with sarcoidosis and cough reported triggers of cough and laryngeal sensations commonly reported by patients with CHS [22]. Triggers such as odours, changes in air temperature, smoke, speech and symptoms of [13]. There was a strong association between self-reported triggers and cough frequency assessed objectively.…”
Section: Cough Reflex Hypersensitivitymentioning
confidence: 87%
See 3 more Smart Citations
“…In the study by Sinha et al, patients with sarcoidosis and cough reported triggers of cough and laryngeal sensations commonly reported by patients with CHS [22]. Triggers such as odours, changes in air temperature, smoke, speech and symptoms of [13]. There was a strong association between self-reported triggers and cough frequency assessed objectively.…”
Section: Cough Reflex Hypersensitivitymentioning
confidence: 87%
“…In an unselected group of patients with pulmonary sarcoidosis, 50 % had an abnormal raised cough frequency assessed objectively with a validated 24-h cough monitor, the Leicester Cough Monitor (LCM) [14]. The average cough frequency was within the range reported for patients with idiopathic chronic cough [13,15]. Sinha et al also investigated the impact of cough on health-related quality of life (HRQOL) with a validated questionnaire: the Leicester Cough Questionnaire (LCQ) [16].…”
Section: Impact Of Coughmentioning
confidence: 97%
See 2 more Smart Citations
“…Sinha et al . reported heightened CRS was associated with lower serum ACE level (r=0.72) though there was no association between serum ACE and objective CFreq ( 4 , 62 ). Meanwhile, Gvozdenovic et al .…”
Section: Sarcoidosismentioning
confidence: 88%